Effect of Different Concentrations of Propofol Used as a Sole Anesthetic on Pupillary Diameter: A Randomized Trial. (August 2020) - Sabourdin, Nada; Meniolle, Fleur; Chemam, Sarah; Rigouzzo, Agnes; Hamza, Jamil; Louvet, Nicolas; Constant, Isabelle
Abstract : BACKGROUND: Pupillometry monitoring under general anesthesia is based on the assumption that pupillary diameter variations reflect the adequacy of the provided analgesia to the intensity of the nociceptive surgical stimulus. The accurate interpretation of pupillometric data requires establishing clearly what the expected baseline unstimulated pupillary diameter at each specific level of hypnosis is. Opioids decrease pupillary diameter in a dose-dependent fashion. In contrast, the effects of hypnotic drugs on pupillary diameter are not well known. Our aim was to describe the potential relationship between propofol predicted effect-site concentrations (Cets) ranging from 1 to 3 µg/mL and pupillary diameter. METHODS: Patients were randomized to receive propofol by target-controlled infusion at a predicted Cet of 1, 2, or 3 µg/mL (groups P1, P2, and P3, respectively). Pupillary diameter measurements were performed after 10 minutes of steady-state propofol infusion at the randomized Cet. No stimulation was performed during the study. Heart rate and bispectral index (BIS) were continuously recorded. RESULTS: Forty patients were included: (13, 14, and 13 in groups P1, P2, and P3, respectively). Mean pupillary diameter was 5.7 mm (1 mm) in group P1, 4.8 mm (1.3 mm) in group P2, and 3.3 mm (0.8 mm) in group P3. Propofol had a dose-dependent effect on pupillary diameter (linear regression R 2 = 0.45, P < .001). Pupillary diameter was positively correlated with the BIS (Spearman r = 0.75 [95% confidence interval (CI), 0.54 to −0.87] P < .001). CONCLUSIONS: From 1 to 3 µg/mL of predicted Cet, propofol has a dose-dependent effect on pupillary diameter. Within this concentrations range, there is a positive correlation between BIS and pupillary diameter. The subcortical effect of propofol on pupillary diameter is correlated to its effect on the cortex. Studies assessing pupillary diameter as a marker of the nociception–antinociception balance should be performed in patients with a standardized depth of hypnosis.